Something Feels Different: Reimagination of Fairy Tales Characters in Once Upon a Crime - Alifa Salsabila; Alma Fadhilahwati; Hilyatuz Zuhdiyah; Nurul Hidayah Septian; Rahima Nur Syafira Arsy (CV. Rustam, 2025)
This study aims to analyze the markers of reimagination in fairy tales, especially through the characters. Reimagination is the process of recreating a story or re-imagining an old version of a story and wrapping it in a new perspective. Character reimagination is seen from the movie Once Upon a Crime (2023). The research data source from characters namely Cinderella (Shinderera), Little Red Riding Hood (Akazukin), Fairy Godmother (Witch Barbara and Witch Tekla), Step Sisters (Anne and Margot), Prince Charming (Prince Gilbert), and Gus Gus the Mouse (Porru). Researchers using methods from Spradley's approach, namely the qualitative descriptive method. This research using main theory from Purnomo, Adila, and Adzhani (2023) about reimagination markers; mutation markers and presentness as well as the reimagination function of both related namely stylistic function, ludic function, medial function, branding function, culture function are seen from this research. The results of this study found that reimagination markers, mutation markers and presentness in the change of iconic characters are dominated by stylistic and cultural functions, indicating that reimagination updates from in the movie Once Upon a Crime not only transformed traditional characters into more modern ones, through altered characterizations, classic stories can be kept alive in a modern cultural context.